The maize shoot ionome: Its interaction partners, predictive power, and genetic determinants. (16th July 2020) - Stich, Benjamin; Benke, Andreas; Schmidt, Maria; Urbany, Claude; Shi, Rongli; von Wirén, Nicolaus
Abstract: An improved understanding of how to manipulate the accumulation and enrichment of mineral elements in aboveground plant tissues holds promise for future resource efficient and sustainable crop production. The objectives of this study were to (a) evaluate the influence of Fe regimes on mineral element concentrations and contents in the maize shoot as well as their correlations, (b) examine the predictive ability of physiological and morphological traits of individual genotypes of the IBM population from the concentration of mineral elements, and (c) identify genetic factors influencing the mineral element composition within and across Fe regimes. We evaluated the concentration and content of 12 mineral elements in shoots of the IBM population grown in sufficient and deficient Fe regimes and found for almost all mineral elements a significant ( α = 0.05) genotypic variance. Across all mineral elements, the variance of genotype*Fe regime interactions was on average even more pronounced. High prediction abilities indicated that mineral elements are powerful predictors of morphological and physiological traits. Furthermore, our results suggest that ZmHMA2/3 and ZmMOT1 are major players in the natural genetic variation of Cd and Mo concentrations and contents of maize shoots, respectively. Abstract : Our results suggest that the shoot ionome is under tight genetic control, and that strong interactions of a genotype with the environment, in our case the Fe regime, are driving the variation for the concentration as well as the content of mineral elements. Furthermore, the high predictive abilities found in this study indicate that mineral elements are powerful predictors of morphological and physiological traits. Their use for the prediction of further, e.g. yield‐related traits, merits to be examined in further studies. We propose that ZmHMA2/3 and ZmMOT1 are major players in the natural genetic variation of Cd and Mo concentrations and contents in maize shoots.